PENGARUH PERMAINAN OUTBOUND TERHADAP KEMAMPUAN PEMECAHAN MASALAH ANAK USIA 4-5 TAHUN DI TK ISLAM AN-NIZHAM - Elvira; Indryani; Rizki Surya Amanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of outbound games on the problem-solving abilities of children aged 4–5 years at TK Islam An-Nizham. This research was motivated by the low problem-solving abilities of children, as many children still depended on teachers or peers when facing challenges during play and learning activities. The research method used was quantitative with a pre-experimental design employing a one-group pretest-posttest design. The sample consisted of 15 children aged 4–5 years from group B1 at TK Islam An-Nizham. Through outbound games, children were provided with direct, enjoyable, and challenging learning experiences that enabled them to recognize problems, try various solutions, cooperate with others, and make simple decisions independently. Thus, it can be concluded that outbound games have an effect on the problem-solving abilities of children aged 4–5 years at TK Islam An-Nizham. This study is expected to serve as an alternative innovative and enjoyable learning activity in developing early childhood cognitive abilities, particularly problem-solving skills